1999
DOI: 10.1118/1.598563
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of polychromatic attenuation using computed tomography reconstructed images

Abstract: This paper presents a procedure for estimating an accurate model of the CT imaging process including spectral effects. As raw projection data are typically unavailable to the end-user, we adopt a post-processing approach that utilizes the reconstructed images themselves. This approach includes errors from x-ray scatter and the nonidealities of the built-in soft tissue correction into the beam characteristics, which is crucial to beam hardening correction algorithms that are designed to be applied directly to C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…The BHC dependence of the size-related measurement error highlights the critical importance of BHC choice prior to any analysis of ρ m . Moreover, CT image reconstruction and algorithm-based beam hardening correction is an active area of research and a variety of studies have reported methodological variations [70, 7789]. Given our results, it is recommended that performance of various mathematical beam-hardening corrections in the use of μCT be further investigated.…”
Section: Discussionmentioning
confidence: 85%
“…The BHC dependence of the size-related measurement error highlights the critical importance of BHC choice prior to any analysis of ρ m . Moreover, CT image reconstruction and algorithm-based beam hardening correction is an active area of research and a variety of studies have reported methodological variations [70, 7789]. Given our results, it is recommended that performance of various mathematical beam-hardening corrections in the use of μCT be further investigated.…”
Section: Discussionmentioning
confidence: 85%
“…It is known that boneapparent density is closely related to the bone mechanical properties [33]. For this work, we intend to develop a clinical system based on the algorithms developed by Yan et al [34,35]. This will allow us to extract precise bone density measurement from CT slices, which can then be translated to bone mechanical properties.…”
Section: Discussionmentioning
confidence: 99%
“…The stability improves slightly, but does not approach the eigenvalue curve for the ͕water, iron͖ set, which has the same number of data points M. Interestingly, including more materials does actually improve the system matrix stability. As pointed out by Yan et al, 9 the stability of the spectrum determination problem should not improve much for more than two materials because there are only two main mechanisms, having their own characteristic energy dependence, for x-ray attenuation in the 100-keV energy range. Indeed, we found that stability did not improve when we used more than two materials, when we employed an idealized model for x-ray attenuation where the attenuation splits cleanly into photoelectric and Compton components with similar energy dependence for all materials.…”
Section: Design Of Ct Measurementsmentioning
confidence: 97%
“…[4][5][6][7][8][9] The same strategy has also been applied to x-ray spectrum estimation for medical linear accelerators for therapeutic beams. 8,[10][11][12][13][14][15] The problem of reconstructing x-ray spectra from transmission data can be formulated as a linear integral equation.…”
Section: Introductionmentioning
confidence: 96%